2017
DOI: 10.1021/jacs.6b12108
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Synergistic Activity When Combining RNAi and Platinum-Based Anticancer Agents

Abstract: RNAi approaches have been widely combined with platinum-based anticancer agents to elucidate cellular responses and to target gene products that mediate acquired resistance. Recent work has demonstrated that platination of siRNA prior to transfection may negatively influence RNAi efficiency based on the position and sequence of its guanosine nucleosides. Here, we used detailed spectroscopic characterization to demonstrate rapid formation of Pt-guanosine adducts within 30 min after coincubation of oxaliplatin [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 66 publications
0
38
0
1
Order By: Relevance
“…Additionally, they have generally relied on drug encapsulation as opposed to chemical conjugation; as a result, these NPs have displayed continuous drug release during their intravascular circulation 10 , which has led to persistent off-target side effects with only mild increases in efficacy 13 . While there are numerous examples of NP-drug conjugates in the literature, to date these formulations have also utilized either conventional or experimental small molecules with similar antitumor activities (i.e., 10–500 nM IC 50 s) 14 , 15 . As only 1–2 wt% of the injected NP dose is typically delivered to tumors after intravenous (IV) administration 16 , large amounts of carrier material are required for therapeutic efficacy, which has, hitherto, stymied clinical translation and/or induced material toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they have generally relied on drug encapsulation as opposed to chemical conjugation; as a result, these NPs have displayed continuous drug release during their intravascular circulation 10 , which has led to persistent off-target side effects with only mild increases in efficacy 13 . While there are numerous examples of NP-drug conjugates in the literature, to date these formulations have also utilized either conventional or experimental small molecules with similar antitumor activities (i.e., 10–500 nM IC 50 s) 14 , 15 . As only 1–2 wt% of the injected NP dose is typically delivered to tumors after intravenous (IV) administration 16 , large amounts of carrier material are required for therapeutic efficacy, which has, hitherto, stymied clinical translation and/or induced material toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments showed strong downregulation of Bcl-2 mRNA levels in MCF-7 and OVCAR-4 breast cancer cell lines. In addition, this formulation induced cell death was up to 100-fold more efficient than the free drugs in all the cancer cell lines tested [70]. However, these NPs were not tested in murine tumor models.…”
Section: Pll-derived Nanosystemsmentioning
confidence: 98%
“…Clinical studies demonstrated that stromal fibroblasts in the tumor microenvironment confer cis-diammineplatinum(II) (CDDP) chemo-resistance, and CD8+ T cells abolish the cancer-associated fibroblast-mediated chemo-resistance through CD8+ T-cell-derived interferon (IFN)-γ (a major effector cytokine of CD8+ T-cell), which reveals the interplay between chemotherapy and immunotherapy. [10][11][12] The clonal expansion of T-cells in the tumor microenvironment correlates with a better response to chemotherapy; 13 therefore, the effectiveness of chemotherapy relies on the induction of a durable anticancer immune response. 14,15 Pre-existing CD8+ T-cells in the tumor microenvironment also predict the efficacy of aPD-1 therapy.…”
Section: Introductionmentioning
confidence: 99%